KETERBUKAAN KOMUNIKASI DALAM MENCIPTAKAN IKLIM KOMUNIKASI YANG KONDUSIF DI PERPUSTAKAAN - Suparna, Putu; Rachmawati, Tine Silvana; Winoto, Yunus (Universitas Padjadjaran, 2013)
The research objective to: 1) determine the openness of communication in creating a climate conducive communication in Kapusipda Buleleng of aspects of communication supervisor; 2) know the openness of communication in creating a climate conducive communication in Kapusipda Buleleng of the communication aspect of subordinates; 3) the implications openness of communication in creating a climate conducive communication in Kapusipda Buleleng. Qualitative research methods using a case study approach. The key informant was manager Kapusipda Buleleng, ten speakers. The results showed as follows: 1) based on the communication aspect boss has not been fully implemented because there are some bosses who never communicate to subordinates, such as the results of the meeting. Ie, the section chief supervisor should have to provide information or to bridge between subordinate to a higher leadership position in the organization; 2) based on the communication aspect subordinate seen already run effectively, which means their communication relationships between subordinates and superiors are effective according to environmental conditions and balanced. The willingness of employers to listen to complaints or difficulty of the work and receive suggestions or ideas presented subordinates by opening the door wide for subordinates; 3) the implications of open communication in creating a climate conducive communication in Kapusipda Buleleng seen their trust, closeness, support, and are willing to listen to the problem, and be willing to accept advantages and disadvantages. Conclusions of research as follows: 1) based on the communication aspect boss has not been fully implemented because there are still some employers at the level of section chief who has not communicating information to a subordinate, for example, the results of the meeting; 2) based on the communication aspect of subordinates seen their communication relationships between subordinates and superiors are effective according to environmental conditions and balanced. The willingness of employers to listen to complaints or difficulty of the work and receive suggestions or ideas presented subordinates by opening the door wide for subordinates; 3) the implications of open communication in creating a climate conducive communication in Kapusipda Buleleng seen their trust, closeness, support, and are willing to listen to the problem, and be willing to accept advantages and disadvantages. Tujuan penelitian untuk : 1) mengetahui keterbukaan komunikasi dalam menciptakan iklim komunikasi yang kondusif di Kapusipda Kabupaten Buleleng dari aspek komunikasi atasan; 2) mengetahui keterbukaan komunikasi dalam menciptakan iklim komunikasi yang kondusif di Kapusipda Kabupaten Buleleng dari aspek komunikasi bawahan ; 3) mengetahui implikasi keterbukaan komunikasi dalam menciptakan iklim komunikasi yang kondusif di Kapusipda Kabupaten Buleleng. Metode penelitian menggunakan metode kualitatif pendekatan studi kasus. Informan kunci adalah pengelola Kapusipda Kabupaten Buleleng, sebanyak sepuluh narasumber. Hasil penelitian menunjukkan sebagai berikut: 1) berdasarkan aspek komunikasi atasan belum sepenuhnya dilaksanakan karena masih terdapat beberapa atasan yang tidak pernah mengkomunikasikan pada bawahan, misalnya hasil rapat. Seyogyanya atasan yakni kepala seksi harus menyediakan informasi atau dapat menjembatani antara bawahan dengan pimpinan yang lebih tinggi lagi kedudukannya dalam organisasi tersebut; 2) berdasarkan aspek komunikasi bawahan terlihat sudah berjalan efektif yang berarti adanya hubungan komunikasi antara bawahan dan atasan yang efektif sesuai kondisi lingkungan dan seimbang. Adanya kesediaan atasan mendengarkan keluhan atau kesulitan pekerjaan dan menerima saran atau gagasan yang disampaikan bawahannya dengan cara membuka pintu lebar-lebar bagi bawahan; 3) implikasi keterbukaan komunikasi dalam menciptakan iklim komunikasi yang kondusif di Kapusipda Kabupaten Buleleng terlihat adanya kepercayaan, kedekatan, dukungan, dan bersedia mendengarkan masalah, serta bersedia menerima kelebihan dan kekurangan. Simpulan penelitian sebagai berikut: 1) berdasarkan aspek komunikasi atasan belum sepenuhnya dilaksanakan karena masih terdapat beberapa atasan pada tingkatan kepala seksi yang belum mengkomunikasi kan informasi ke bawahan, misalnya hasil rapat; 2) berdasarkan aspek komunikasi bawahan terlihat adanya hubungan komunikasi antara bawahan dan atasan yang efektif sesuai kondisi lingkungan dan seimbang. Adanya kesediaan atasan mendengarkan keluhan atau kesulitan pekerjaan dan menerima saran atau gagasan yang disampaikan bawahannya dengan cara membuka pintu lebar-lebar bagi bawahan; 3) implikasi keterbukaan komunikasi dalam menciptakan iklim komunikasi yang kondusif di Kapusipda Kabupaten Buleleng terlihat adanya kepercayaan, kedekatan, dukungan, dan bersedia mendengarkan masalah, serta bersedia menerima kelebihan dan kekurangan.